Virtually Connected: Do Shared Novel Activities in Virtual Reality Enhance Self-Expansion and Relationship Quality? - Rhonda N. Balzarini; Anya Sharma; Amy Muise (Behavioral Sciences)
According to self-expansion theory, sharing novel experiences with a romantic partner can help prevent boredom and maintain relationship quality. However, in today’s globalized modern world, partners spend less time together and are more likely to live apart than in previous generations, limiting opportunities for shared novel experiences. In two in-lab experiments, we tested whether shared novel activities in virtual reality (VR) could facilitate self-expansion, reduce boredom, and enhance relationship quality. In Study 1, couples (N = 183) engaged in a shared novel and exciting activity in either VR or over video. Participants in the VR condition reported greater presence (i.e., felt like they were in the same space as their partner) and were less bored during the interaction compared to the video condition, though no main effects emerged for reports of self-expansion or relationship quality (relationship satisfaction and closeness). Consistent with predictions, people who reported more presence, in turn, reported greater self-expansion, less boredom, and greater relationship quality. In Study 2, couples (N = 141) engaged in a novel and exciting or a mundane experience in VR. Results were mixed such that participants in the novel VR condition reported less boredom and greater closeness post-interaction, though no effects emerged for self-expansion or relationship satisfaction. In exploratory analyses accounting for immersion, couples who engaged in the novel virtual experience reported more self-expansion, less boredom, and greater closeness. The findings suggest that virtual interactions may have less potential than in-person interaction to promote self-expansion but offer interesting future directions given VR’s ability to enhance presence beyond video interactions.